2013
DOI: 10.1111/jabr.12013
|View full text |Cite
|
Sign up to set email alerts
|

Parent Depression Symptoms and Child Temperament Outcomes: A Family Study Approach

Abstract: Parent personality and depression, family conflict, and child temperament were examined in a family study design including two children 2.5–5.5 years of age. Sibling resemblance for temperament was also investigated. Parent personality and family conflict had minimal significance for child temperament outcomes. However, parent depression was associated with higher child activity level and anger, and lower inhibitory control. These findings were supported by more rigorous regression analyses that included paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 65 publications
(85 reference statements)
4
10
1
Order By: Relevance
“…In this sample, we previously found that maternal depression (as assessed in the same manner as the current study) was significantly associated with parent-rated negative temperament traits in children (Gagne, Spann, et al, 2013), suggesting that mothers with higher levels of depression symptoms have more negative views of their children's behaviour. Similar to child age, the bivariate results related to maternal mental health symptoms in the present study were contextualized depending on mode of IC assessment.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In this sample, we previously found that maternal depression (as assessed in the same manner as the current study) was significantly associated with parent-rated negative temperament traits in children (Gagne, Spann, et al, 2013), suggesting that mothers with higher levels of depression symptoms have more negative views of their children's behaviour. Similar to child age, the bivariate results related to maternal mental health symptoms in the present study were contextualized depending on mode of IC assessment.…”
Section: Discussionsupporting
confidence: 65%
“…Various parental factors including personality (e.g., neuroticism), emotion/affect, parenting style, substance use, and mental health symptoms have been examined in previous studies. In preliminary analyses with this sample using only questionnaire data, parent depressive symptoms were associated with lower parent‐reported IC in preschool‐aged children (Gagne, Spann, & Prater, ). Several other studies have examined the effects of parent depressive symptoms on child IC and related variables (i.e., other temperament dimensions and behavioural maladjustment).…”
Section: Introductionmentioning
confidence: 99%
“…Both bivariate correlational and regression analyses showed that parent depressive symptoms predicted child AL, as previous studies have shown (Gagne, Spann, et al., ; Gartstein & Fagot, ; Goodman et al., ; Goodman & Gotlib, ; Gunlicks & Weissman, ; Hannington et al., ; Hopkins et al., ; Lavigne et al., ; Rosenbaum et al., ; Slatcher & Trentacosta, ; Xu et al., ) . Parental depression symptoms did not predict child fear, possibly a function of examining this relationship from a broad trait perspective.…”
Section: Discussionsupporting
confidence: 74%
“…For example, previous studies have acknowledged predictive relationships between parental mental health status and child temperament outcomes (Achtergarde, Postert, Wessing, Romer, & Muller, ; Gagne, Spann, et al., ; Rutter & Quinton, ). Several investigations have indicated that depressed mothers perceive their children as being more difficult than nondepressed mothers (Edhborg, Seimyr, Lundh, & Widstrom, ; Gagne, Spann, et al., ; Gunlicks & Weissman, ; Hannington, Ramchandani, & Stein, ; Ventura & Stevenson, ). Specifically, parental depressive symptoms are associated with increased fearfulness and AL (Gagne, Spann, et al., ; Goodman, Adamson, Riniti, & Cole, ; Goodman & Gotlib, ; Gunlicks & Weissman, ; Hannington et al., ; Hopkins, Lavigne, Gouze, LeBailly, & Bryant, ; Lavigne et al., ; Rosenbaum et al., ; Xu, Neece, & Parker, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation